Anesthetic Management of Laparoscopic Adrenalectomy for a Patient with Concomitant Pheochromocytoma and Bilateral Carotid Artery Stenosis. (7th January 2023) - Michaud, Kristina L.; Thiele, Robert H.; Forkin, Katherine T.
Abstract : Symptomatic carotid stenosis and pheochromocytoma both require timely surgical intervention. Following a transient ischemic attack (TIA), a 46-year-old man was diagnosed with bilateral carotid artery stenosis and scheduled for carotid endarterectomy. He was a poor candidate for minimally invasive options due to prior neck radiation. Simultaneously, he began experiencing difficulty with diabetes management and elevated blood pressures and was ultimately diagnosed with pheochromocytoma. This unique situation required coordination to determine the appropriate timing of the two interventions. This case highlights the importance of communication and coordination amongst medical specialists and consideration for anesthetic management of patients with concomitant pheochromocytoma and carotid stenosis.